Govern like us : U.S. expectations of poor countries - Thomas, Melissa Annette (Columbia University Press, 2015)
Informed by years of fieldwork and drawing on practitioner work and academic scholarship in politics, economics, law, and history, this book explains the origins of poor governments in the formation of the modern state system and describes the way they govern. It argues that, surprisingly, the effort to stigmatise and criminalise the governance of the poor is both fruitless and destabilising. The United States requires a more effective foreign policy to engage poor governments and acknowledge how they govern.